Soft skill development for community leadership in participatory groundwater management - International Water Management Institute; Centre for microFinance (CmF); People's Education and Development Organization (PEDO); Professional Assistance for Development Action (PRADAN) (International Water Management Institute, 2025)
The Soft Skill Training Module for Community Leadership in Participatory Groundwater Management (PGWM) was developed to complement the Atal Bhujal Yojana (ATAL JAL), a key policy of the Government of India that designates communities as resource managers for the common-pool resource of groundwater. This module was developed by the International Water Management Institute (IWMI) in partnership with Centre for Microfinance (CmF) and Professional Assistance for Development Action (PRADAN).